Linkage of Monetary Policy and Islamic Capital Market: The Case of Indonesia - Quthbi, Zainul Hasan (Journal of Islamic Economics Lariba, 2019)
The study aims to examine the linkage of monetary policy and the Islamic stock market in Indonesia. Monetary policy variables are used in this study, namely, interest rate, exchange rate, and money supply (M2). Besides, the foreign interest rate is included as measured by FFR. At the same time, the shari’a index is used, namely Jakarta Islamic Index (JII). In the analysis, this study adopts the cointegration test, Granger causality test, and VECM. This study showed a negative long-term relationship between the variable interest rate and M2 to the JII stock price. The exchange rate variable has a positive long-term relationship with the JII stock price. While the foreign interest rate variable has a short-tem relation to the JII stock price, it doesn’t have a long term relationship.